Memory, music, and religion: Morocco's mystical chanters - Waugh, Earle H. (Studies in comparative religion, 2005)
Examining foundations : the formation of the Islamic chanter tradition -- The Islamic engagement with memory : remembrance as a way of knowing -- The chanter's religious scripts : the transformation of memory's heritage -- The chanter's classical text : tools for the master of memory -- Alternative and visionary pasts : the impact of other memories -- Remembered sacred sounds : the music of the Munshidūn -- The contemporary Munshid : between memory and attestation -- The Munshidūn, memory, and religion.